Resource management in a changing and uncertain climate. Issue 1 (10th October 2008) - Lawler, Joshua J; Tear, Timothy H; Pyke, Chris; Shaw, M Rebecca; Gonzalez, Patrick; Kareiva, Peter; Hansen, Lara; Hannah, Lee; Klausmeyer, Kirk; Aldous, Allison; Bienz, Craig; Pearsall, Sam
Abstract : Climate change is altering ecological systems throughout the world. Managing these systems in a way that ignores climate change will likely fail to meet management objectives. The uncertainty in projected climate‐change impacts is one of the greatest challenges facing managers attempting to address global change. In order to select successful management strategies, managers need to understand the uncertainty inherent in projected climate impacts and how these uncertainties affect the outcomes of management activities. Perhaps the most important tool for managing ecological systems in the face of climate change is active adaptive management, in which systems are closely monitored and management strategies are altered to address expected and ongoing changes. Here, we discuss the uncertainty inherent in different types of data on potential climate impacts and explore climate projections and potential management responses at three sites in North America. The Central Valley of California, the headwaters of the Klamath River in Oregon, and the barrier islands and sounds of North Carolina each face a different set of challenges with respect to climate change. Using these three sites, we provide specific examples of how managers are already beginning to address the threat of climate change in the face of varying levels of uncertainty.